Nutritional Status among the Women and Children in Bangladesh: Implications for Health Social Work Practice - Hanumant Waghmare; Sudhir Maske; Pooja Gaigaware (Social Work and Society)
Undernutrition is a serious public health concern in several Asian countries, especially in Bangladesh. This paper presents the findings of a study conducted to identify the factors influencing the nutritional status of women and children under the age of five, using data from the Demographic Health Survey. The study also explores potential social work interventions to address these issues through civil society and advocacy efforts. Despite government initiatives, the nutritional status of women and children remains a major concern in Bangladesh. The study assesses the nutritional status of women based on their Body Mass Index (BMI) and reports a decrease in the prevalence of anemia by 15.4% among women and 32.2% among children. Furthermore, the study indicates that nutritional policies and programs have had a positive impact on the nutritional status of women and children. The findings highlight the necessity of a robust support system that prioritizes a multi-sectoral approach to address undernutrition. The study emphasizes the importance of collective and coordinated efforts for the successful implementation of nutritional policies. Additionally, the study stresses the significance of understanding and perspectives about nutrition for social work researchers and practitioners to effectively address health-centered social work practices. Ultimately, the study underscores the direct link between health and nutrition and the broader goals of human well-being, inclusive, and sustainable development.